2003
DOI: 10.1034/j.1600-0706.2003.12075.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore damage to sagebrush induces resistance in wild tobacco: evidence for eavesdropping between plants

Abstract: Whether plants respond to cues produced by neighbors has been a topic of much debate. Recent evidence suggests that wild tobacco plants transplanted near experimentally clipped sagebrush neighbors suffer less leaf herbivory than tobacco controls with unclipped neighbors. Here we expand these results by showing evidence for induced resistance in naturally rooted tobacco when sagebrush neighbors are clipped either with scissors or damaged with actual herbivores. Tobacco plants with sagebrush neighbors clipped in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 41 publications
(60 reference statements)
2
117
1
2
Order By: Relevance
“…Aboveground, VOC-mediated plant-plant interactions are reported to occur over distances that vary depending on the plant species and environmental parameters (such as atmospheric ozone concentration) (Blande et al 2010). In field experiments involving sagebrush and tobacco, plant-plant signalling was demonstrated to occur over distances ranging from 10 cm (sagebrush to tobacco) to 60 cm (sagebrush to sagebrush) (Karban et al 2003(Karban et al , 2006. Similarly, the secretion of extra floral nectar by lima bean leaves was reported to occur in receiver plants located up to 50 cm away from the emitter (Heil and Adame-Álvarez 2010).…”
Section: Environmental Fate Of Root-emitted Vocsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aboveground, VOC-mediated plant-plant interactions are reported to occur over distances that vary depending on the plant species and environmental parameters (such as atmospheric ozone concentration) (Blande et al 2010). In field experiments involving sagebrush and tobacco, plant-plant signalling was demonstrated to occur over distances ranging from 10 cm (sagebrush to tobacco) to 60 cm (sagebrush to sagebrush) (Karban et al 2003(Karban et al , 2006. Similarly, the secretion of extra floral nectar by lima bean leaves was reported to occur in receiver plants located up to 50 cm away from the emitter (Heil and Adame-Álvarez 2010).…”
Section: Environmental Fate Of Root-emitted Vocsmentioning
confidence: 99%
“…Volatile compounds Fig. 1 emitted by conspecifics or originating from individuals belonging to another plant species have been shown to promote the induction of direct and indirect defences in undamaged neighbouring plants (Dicke et al 2003;Heil and Karban 2010), thus increasing their resistance to insect herbivores (Karban et al 2000;Tscharntke et al 2001;Karban et al 2003Karban et al , 2004Rodriguez-Saona et al 2009) or phytopathogens (Shulaev et al 1997;Yi et al 2009;GirĂłn-Calva et al 2012). Volatiles emitted by mechanically damaged or herbivore-attacked plants have also been shown to be able to prime neighbouring plants or parts of the same plant for faster and greater responsiveness to subsequent mechanical stress or herbivore attack, enabling the receiver plants to respond more efficiently when they are attacked (Engelberth et al 2004;Ton et al 2006;Heil and Kost 2006;Frost et al 2007Frost et al , 2008bLi et al 2012;Erb et al 2015).…”
Section: Vocs Play Important Ecological Roles In Plant-plant Interactmentioning
confidence: 99%
“…Although HIPVs are also known to mediate a diverse array of interactions between plants and insects (Turlings et al, 1990;De Moraes et al, 1998;Hoballah and Turlings, 2001;De Moraes et al, 2001), the role of volatiles in signaling between plants has been one of the most fascinating and controversial topics in modern ecology (Baldwin and Schultz, 1983;Fowler and Lawton, 1985;Farmer and Ryan, 1990;Shonle and Bergelson, 1995;Karban and Baldwin, 1997;Agrawal, 2000;Bruin and Dicke, 2001;Baldwin et al, 2002Baldwin et al, , 2006Karban et al, 2003;Dudareva et al, 2006). One recurring point of controversy has been the distance over which HIPV signals can be received by plants (Baldwin et al, 2002;Karban et al, 2003;Kessler et al, 2006). Recent work has shown that vascular constraints on systemic induction can be overcome with HIPVs (Karban et al, 2006;Heil and Silva Bueno, 2007;Frost et al, 2007), as hypothesized by both Farmer (2001) and Orians (2005).…”
Section: Signaling Cues For Priming Antiherbivore Defensesmentioning
confidence: 99%
“…Arimura et al, 2000;Dolch and Tscharntke, 2000;Karban and Maron, 2002;Karban et al, 2003;Engelberth et al, 2004), and particularly in overcoming potential constraints on the internal (vascular) transmission of wound signals imposed by plants' modular architecture (Karban et al, 2006;Frost et al, 2007;Heil and Silva Bueno, 2007;Rodriguez-Saona et al, 2009).…”
Section: Alarm Signals In Plantsmentioning
confidence: 99%